Soy extracts suppressed iodine uptake and stimulated the production of autoimmunogen in rat thyrocytes. (June 2013) - Tran, Lisa; Hammuda, Mariam; Wood, Carla; Xiao, Chao Wu
Soy consumption is associated with thyroid disorders such as hypothyroidism, goiter, and autoimmune thyroid disease (ATD) as well as increased iodine requirement in certain cases. However, the anti-thyroid component(s) in soy are yet to be identified and the molecular mechanism(s) involved remain unclear. This study examined the effects of soy isoflavones (ISF) on iodide uptake and expression of thyroglobulin (Tg) and sodium/iodide symporter (NIS) in thyrocytes. Fischer rat thyroid cells (FRTL) were treated with Novasoy (a soy alcohol extract containing 30% ISF) or major ISF aglycones or glycosides for 24 h. Iodide uptake was measured by a colorimetric assay. The protein level of Tg and NIS was measured by Western blotting. Cytotoxicity of tested compounds was determined by the MTT cell proliferation assay. Iodide uptake in FRTL cells was dose-dependently suppressed by Novasoy added into the cell culture (10, 25, or 50 µg/mL, P  < 0.05). However, neither the major ISF aglycones nor glycosides alone or in combination had similar effects. Novasoy (up to 200 µg/mL) had no cytotoxic effect. Novasoy (1, 10, and 50 µg/mL) and genistein (1 and 10 µM) markedly increased the protein content of a 40 kDa Tg fragment (P40, a known autoimmunogen) and non-glycosylated NIS in the FRTL cells ( P  < 0.05). Overall, this study demonstrated that the alcohol soluble component(s) other than the major ISF in soy remarkably inhibited iodide uptake in the FRTL cells. Soy ISF, particularly genistein, induced the production of P40, which might be responsible for the higher incidence of ATD reported in soy infant formula-fed children.